Implementasi Kepemimpinan dan Eksklusivisme pada Organisasional Di Universitas Nahdlatul Wathan Mataram - Sofian Hadi (Universitas Bumigora, 2021)
The purpose of this study was to see the implementation of leadership and exclusivism that occurred at Nahdlatul Wathan University Mataram. The research method used is descriptive using a questionnaire instrument given to 116 respondents with 11 question indicators. The analysis used is descriptive quantitative data analysis. The results of this study indicate: (1) Implementation of leadership that prioritizes two-way communication can form an institution with high organizational structure for its members. And become a fortress to minimize various factors that can weaken the implementation of leadership itself. And (2) Exclusivism which has a tendency to weaken both leadership and organization cannot affect it fundamentally, if the feelings of every member of the organization have been formed from the start to become a member of the organization at Nahdlatul Wathan University. Mataram.